Fuzzy Service Quality dalam Analisis Kepuasan Pengunjung terhadap Kualitas Pelayanan Objek Wisata Kapalo Banda - Dipinta, Yona; Helma, Helma (Journal of Mathematics UNP, 2022)
Kapalo Banda is one of the tourist attractions located in Fifty Cities Regency. The research conducted in Kapalo Banda is related to visitor satisfaction for the elements of the services provided by applying the fuzzy service quality method. Fuzzy service quality is a combination of service quality methods and fuzzy logic. The service quality method can measure service quality based on five dimensions, namely: physical evidence (tangible), reliability (reliability), responsiveness (responsiveness), assurance (assurance), empathy (emphaty). Based on the results of this study, it was found that visitors were not satisfied with the services they received. This is because there are five positive gap values and ten negative gap values. Therefore, it is necessary to make improvements. The attribute that is used as a reference for improvement is the one with the highest negative gap value.